Partial Extraction Therapy with Early Implant Placement in the Esthetic Zone: A Clinical Case Report - Saleh N. Almohammed; Reem S. Abdel-Hafez; Duaa D. Ailabouni (Case Reports in Dentistry)
Immediate replacement of teeth designated for extraction is an appealing treatment rationale for both the patient and the operator. However, it has been associated with a greater risk of facial recession and compromised soft-tissue esthetics. Partial extraction therapy (PET) or synonymously socket shield technique (SST) or root membrane technique (RMT) has been proposed to conserve the facial alveolar contour and soft-tissue esthetics. In this article, a special case is described where a root membrane was used to prevent the modeling of the facial aspect of the extraction socket. Partial extraction was performed allowing the socket with the facial root membrane in situ to partially heal for 8 weeks before implant placement. Successful integration and restoration were achieved with very minimal hard- and soft-tissue changes, accentuating satisfactory esthetic results as dictated by objective esthetic assessment. PET with early implant placement may be considered a viable treatment option for selected cases.